La «fobìa romana»: un commento agli studi freudiani di Sebastiano Timpanaro - Roberto Altamura (Il sogno della farfalla, 2019)
These notes have a double intent: on the one hand they offer the reader a very brief orientation on the figure and work of an important Italian philosopher and philologist, Sebastiano Timpanaro (Parma 1923-Florence 2000); on the other hand, they take a deep look at a particular work, published for the first time in 1992 and re-edited in 2006: The «Roman Phobia» and other writings on Freud and Meringer. An expert in philology (in particular a master of “textual critique”), Timpanaro then dedicated himself to Marxism and Psychoanalisys. In a work translated into English, of 1974 (The Freudian lapsus. Psychoanalisys and a textual critique, re-edited in 2002), he submits “Freud’s master proposition”, that is the Viennese’s proposition that links displacement, dream interpretation and daily life psychopathology, to a pitiless and demolishing criticism. This research has been received with great favour by the psychiatric epistemologist A. Grumbaum in his main work The Foundations of Psychoanalisys (1984). In the 1992 work, apart from concentrating critically on a significant problem of Freud’s life, his phobia about reaching the eternal city, he offers a methodological and radical refusal of every “contamination” between Freudism and Marxism. Maybe the sentence that best synthesizes this thought is the following: «If I must give a definition, as brief and correct as possible, of the typical “Western Marxist”, I would say: “a person that is firmly convinced that Freud is always right”».